Young Children's Food-Related Receptive Language and Acceptance of a Novel Food. (7th June 2021) - Shapiro, Allison; Flesher, Abigail; Lattanzi, Kendal; Charlifue-Smith, Renee; Johnson, Susan
Abstract: Objectives: Little inquiry has been undertaken regarding the interface of children's development of eating behaviors and their understanding of food-related (FR) words. Thus, we explored the relationship between young children's understanding of FR vocabulary (FR receptive language) and their acceptance of a novel food. Methods: Caregivers (n = 35) and children ages 7–24 mo (n = 12 infants age <12 mo; n = 23 toddlers age ≥12 mo) participated in a study in which caregivers offered a novel food (nutrition supplement added to infant oatmeal) to their children. Novel food acceptance was measured as g consumed. The Communicative Development Inventory assessed caregiver perceptions of infants' understanding of 154 words related to food and eating (FR receptive language). A linear regression model with FR receptive language, age (toddler vs. infant) and a FR receptive language-by-age interaction was used to predict acceptance of the novel food. Covariates included infant sex and BMI z-score and a p < 0.1 was chosen for this exploratory study. Results: As expected, caregivers reported that infants understood fewer words as compared to toddlers (median [IQR]; 7 [13] vs. 33 [46], respectively). The relationship between FR receptive language and novel food acceptance differed by age (F = 8.08, p = 0.01). Among toddlers, greater FR receptive language (more food-related words understood) was associated with greater novel food acceptance (β [95% CI], 0.22g [−0.04, 0.49], p = 0.09). In younger infants, greater FR receptive language was associated with lower novel food acceptance (−0.80g [−1.53, −0.07], p = 0.03). Conclusions: Receptive language facilitates children's understanding of their environment and contributes to shaping their behavior. Our preliminary findings suggest that greater FR receptive language may facilitate acceptance of novel food in toddlers. Younger infants were perceived to understand few words and may not have enough receptive language to positively influence food acceptance. Funding Sources: This work was supported by the Government of Canada, as part of the Business Platform for Nutrition Research (BPNR) hosted by the Global Alliance for Improved Nutrition.